2001
DOI: 10.1002/j.2162-6057.2001.tb01224.x
|View full text |Cite
|
Sign up to set email alerts
|

Do Time Press, Stimulus, and Creative Prompt Influence the Divergent Production of Undergraduate Students? Yes, Yes, and No, Not Very Much

Abstract: This study examined the influence of time press, specific stimulus, and type of creativity prompt on fluency and flexibility scores of 75 undergraduates randomly assigned to condition. Three stimuli were administered, in three time allotments (2.5, 5.0, and 7.5 min), counterbalanced with three types of prompt intended to elicit higher fluency, flexibility, or originality scores. Dependent variables were fluency and flexibility scores.The results suggest that time press has a strong, and typically linear influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…A recent study using 12 divergent thinking tests and 12 reasoning tasks, half of each under time restrictions, also found that timed versus untimed test‐taking played a minor role in influencing the results of divergent thinking and intelligence (Preckel, Wermer, & Spinath, ). Another study found an effect of time effect on creativity scores, but revealed that the rate of divergent production was essentially the same in the first, second, and third time interval of 2.5 minutes (Morse, Morse, & Johns, ). So our time limit of 2 minutes should be sufficient for the production of meaningful ideas for comparison purposes.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study using 12 divergent thinking tests and 12 reasoning tasks, half of each under time restrictions, also found that timed versus untimed test‐taking played a minor role in influencing the results of divergent thinking and intelligence (Preckel, Wermer, & Spinath, ). Another study found an effect of time effect on creativity scores, but revealed that the rate of divergent production was essentially the same in the first, second, and third time interval of 2.5 minutes (Morse, Morse, & Johns, ). So our time limit of 2 minutes should be sufficient for the production of meaningful ideas for comparison purposes.…”
Section: Methodsmentioning
confidence: 99%
“…First, participants completed a brief measure that assessed their current mood, the Positive and Negative Affect Schedule (PANAS, (Watson & Clark, 1991)). They then completed a divergent thinking measure (Morse, Morse, & Johns, 2001) that required them to come up with as many responses as possible to three items (e.g., uses for a shipment of gloves that only contained left-handed ones). This divergent thinking task was given before the next measure, a word-stem completion task, in order to reduce suspicion as to its true purpose as a manipulation check.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have found that time constraints limit the number of ideas generated as well as the quality of those ideas (Morse, Morse, & Johns, 2001). Therefore, it is not surprising to find that attitudes toward ideation can play a key role in idea generation.…”
Section: Generation Of Alternatives/solution Generationmentioning
confidence: 98%